2018
DOI: 10.3390/s18040955
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Beacon and Event-Driven Messages in Vehicular Platoons through Token-Based Strategies

Abstract: Timely and reliable inter-vehicle communications is a critical requirement to support traffic safety applications, such as vehicle platooning. Furthermore, low-delay communications allow the platoon to react quickly to unexpected events. In this scope, having a predictable and highly effective medium access control (MAC) method is of utmost importance. However, the currently available IEEE 802.11p technology is unable to adequately address these challenges. In this paper, we propose a MAC method especially ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Balador et al [55] have offered the supporting beacon based event driven message transmission in the vehicular network. It proposes the three distinct methods for the event driven message transmission.…”
Section: Safety Message Broadcastingmentioning
confidence: 99%
“…Balador et al [55] have offered the supporting beacon based event driven message transmission in the vehicular network. It proposes the three distinct methods for the event driven message transmission.…”
Section: Safety Message Broadcastingmentioning
confidence: 99%
“…Let us first focus on the average duration before a reallocation is performed. Following the algorithm at the MAC layer, the [5][6][7][8][9][10][11][12][13][14][15] Table 1 are used for all the other settings.…”
Section: A Focus On Specific Metricsmentioning
confidence: 99%
“…To cope with this limitation and to provide an in-depth discussion of Mode 4, here we focus on the main parameters defined at the PHY and MAC layers, considering both those that can be adjusted by specification and those that are instead mandate to a given value. The study will focus on the semi-persistent scheduling (SPS) related to the cooperative awareness service, which is the periodic broadcast of updated information by all vehicles about their status and movements and is at the basis of most of the applications foreseen for connected vehicles [12], [13]. The impact of each parameter and its optimal setting is derived through large-scale simulations in three realistic scenarios with hundred of nodes, using LTEV2Vsim [14].…”
Section: Introductionmentioning
confidence: 99%
“…The data are collected by the member vehicles and aggregated by the head vehicle before they are transmitted to a server. In [ 23 ], Balador et al proposed a beacon-based medium access control (MAC) protocol in a platoon. The simulations have demonstrated that the proposed protocol can enhance reliability and ensure the low-delay transmission for safety applications in intelligent traffic system (ITS).…”
Section: Related Workmentioning
confidence: 99%